PERAN MAJELIS TAKLIM AL ASHAB DALAM MEMBINA AKHLAK REMAJA DI KELURAHAN BABAKAN KECAMATAN SANDUBAYA KOTA MATARAM - Y Satria Hafizil Khalil (Maharah: Journal of Islamic Education Teaching and Learning, 2024)
This research aims to determine the role of the al Ashab Taklim Council in fostering adolescent morals. The research uses descriptive qualitative research methods to examine problems or phenomena in depth. Observation, interviews and documentation were used as data collection techniques. Meanwhile, data validity techniques use triangulation of techniques and sources. As for the research results, 1. a. As a forum for religious life, it can be fostered and developed to build a society that is devoted to Allah SWT. By holding activities 1) Reading Ratib Al Athos, the Book of Maulid Ad Dhiyaulami and Taklim. The method of moral development carried out by the Al Ashab Taklim Council. First, a word of advice. The role of the al Ashab Taklim Council in Advice is to provide usawatun hasanah in the form of kind words, gentleness and motivation to discipline your time by increasing your istigfar to Allah and praying to the Prophet Muhammad SAW. Second, example. The role of the al Ashab taklim assembly in exemplary behavior is as follows: Istiqomah attending the taklim assembly. Third, habituation. The role of the Al Ashab Taklim Council in habits such as: Getting used to saying hello and getting used to behaving politely. b. As a Spiritual Recreation Park using Rihlah Syariah/Grave Pilgrimage. c. Building friendship (house to house).